2008
DOI: 10.1021/jf800801k
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Based Screening Identifies Compounds from the Stem of Momordica charantia that Overcome Insulin Resistance and Activate AMP-Activated Protein Kinase

Abstract: Treatment of insulin resistance is a critical strategy in the prevention and management of type 2 diabetes. The crude extracts from all parts of Momordica charantia L. have been reported by many studies for the effective treatment of diabetes and related complications. However, the exact ingredients responsible for the hypoglycemic effect and the underlying mechanism of their actions have not been well characterized because of the lack of a proper assay and screening system. A new cell-based, nonradioactive, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 32 publications
3
50
0
4
Order By: Relevance
“…4 Among Mexican patients with diabetes who use CAM therapies, 94.2% used herbal remedies, while the remaining 5.8% used other treatments. 5 Similar findings were also reported by other surveys across the world with differences in the herbs and supplements used based on the cultural and regional variation.…”
supporting
confidence: 86%
“…4 Among Mexican patients with diabetes who use CAM therapies, 94.2% used herbal remedies, while the remaining 5.8% used other treatments. 5 Similar findings were also reported by other surveys across the world with differences in the herbs and supplements used based on the cultural and regional variation.…”
supporting
confidence: 86%
“…Some studies also claimed that the hypoglycaemic effect of M. charantia was comparable with oral medications such as tolbutamide [70,91] , chlorpropamide and glibenclamide [92,93] . Abundant biochemical data have shed light upon possible mechanisms of the anti-diabetic actions of M. charantia with the recurring theme being activation of the AMP-activated protein kinase system [94][95][96][97] . Other studies suggested a role of the a-and g-peroxisome proliferator-activated receptors (PPARa and PPARg) which are pivotal in lipid and glucose haemostasis and may mitigate insulin resistance [98,99] .…”
Section: Animal Studies Of M Charantiamentioning
confidence: 99%
“…Effect of monoterpenes on total glucose uptake in 3T3-L1 adipocytes were assessed as described by Cheng, Huang, Chang, Tsai, and Chou (2008) with slight modifications. 3T3-L1 pre-adipocytes were seeded in 96-well plates at a density of 20,000 cells/well and induced to differentiate into mature adipocytes.…”
Section: Total Glucose Uptake Assaymentioning
confidence: 99%